STUDENTS’ PERSPECTIVES AND MOTIVATION TOWARDS STORY JUMPER ON CREATIVE WRITING - Nur Athirah binti Mohammad; Hamidah Yamat (Jurnal Penyelidikan Sains Sosial, 2020)
Creative writing is not an easy task; what more is writing an essay in the target language. Creative writing is one of the compulsory questions. Hence, various measures have taken or techniques introduced to help students perform better in creative writing. This paper presents and discusses a study on the use of Story Jumper in a writing classroom to investigate students’ perspective on story jumper and motivation in creative writing. A quantitative experimental design was employed involving thirty-six form five student in a secondary school in Pahang. Students’ perspectives and motivation were measured using an adapted survey and analysed using SPSS 21. Findings show that the students perceived having positive perspectives and motivation while their writing after using Story Jumper showed more details and information provided. Its concluded that Story Jumper is one of the techniques that can apply to motivate students to write and increase their ideas to write creatively. It further implies that teachers need to continuously find means to motivate their students to writes that will improve their writing performance.